Acceptability of veggie bread among Lebanese adults - Chanbour, Asma; Hassan, Hussein F.; Kreidieh, Dima; Khazaal, Salma; Osaili, Tareq; El Omari, Khaled; El Darra, Nada (Frontiers in Public Health, 2025)
Bread is a staple food in Lebanon, but traditional refined wheat bread lacks essential nutrients. Incorporating vegetables as functional ingredients has gained interest in enhancing its nutritional profile. This study aimed to assess Lebanese adults' willingness to adopt veggie bread, given its novelty in Lebanon. An English-Arabic survey was administered to 750 Lebanese adults to evaluate bread consumption and their willingness to switch to veggie bread. Statistical analyses included frequency distribution, response percentages, internal consistency (Cronbach's alpha), and the Chi-square test for independence to examine associations between sociodemographic factors and willingness to switch. Four veggie breads were obtained and a sensory evaluation was conducted with 50 panelists using hedonic ranking, preference ranking, and food action/attitude rating tests. The sociodemographic profile of the 750 participants revealed a predominance of females (82.1%), with the majority being young adults aged 18–30 years (47.3%). The study found that freshness (64%), use-by-date (65.3%), and taste (60.7%) were the most important factors in bread selection, with price rated as “very important” by 28.5% of participants. The study found that 51.2% valued fiber addition in bread, 37.5% considered veggie bread healthier, and 52.8% would switch to veggie bread if it offered more nutrients. Statistical analysis revealed significant associations between sociodemographic factors and participants' willingness to switch to veggie bread. Education, occupation, income, and family size influenced perceptions of veggie bread's safety, health benefits, and appeal. Carrot bread received the highest acceptance and preference, followed by spinach and cabbage bread, while beetroot bread had the lowest acceptance. These results were statistically significant, as indicated by the Chi-square test (p < 0.008) for the hedonic ratings and p < 0.001 for the preference ranking. Out of 50 panelists, the majority expressed positive attitudes toward veggie bread, with 17 stating they would eat it at every opportunity and 12 frequently. This study highlights the growing interest in veggie bread among Lebanese adults, with significant factors such as health benefits and nutrition influencing their willingness to switch.